Formación continua de profesores para una orientación CTS de la enseñanza de química. Un estudio de caso - Martins, Isabel P. (2022)
This paper summarily exposes the general characteristics of the emergent science education in the treshold of the twenty century and some socio-economical conditions that contextualiza it. It is supposed that its subjacent finalities frame in the STS movement and that this contibutes to profile new methodologies and focus in science teaching, with the aim of the development pupils scientific (and technological) skills.